15.1k views
0 votes
Evaluate and simplify the expression when A=4 and b=- 1

Evaluate and simplify the expression when A=4 and b=- 1-example-1
User Bruce Dean
by
5.7k points

1 Answer

4 votes

Since the given expression is


(5-2(a+3b))/(2)

Since a = 4 and b = -1

Substitute them in the expression above


\begin{gathered} (5-2(a+3b))/(2)=(5-2(4+3\lbrack-1\rbrack))/(2) \\ =(5-2(4+\lbrack-3\rbrack))/(2) \end{gathered}

Simplify the bracket


\begin{gathered} (5-2(4-3))/(2)=(5-2(1))/(2) \\ =(5-2)/(2) \end{gathered}

Simplify the numerator


(5-2)/(2)=(3)/(2)

The missing is 3

User Narcolessico
by
6.2k points